The Effect of Weather Elements on the Intensity of Leaf Blight Disease Caused by Phytophthora colocasiae in Taro - Akbar, Faishal; Sastrahidayat, Ika Rochdjatun; Djauhari, Syamsuddin (Research Journal of Life Science, 2021)
Leaf blight Phytophthora colocasiae is one of the main diseases in taro plants which can reduce production yield significantly. Weather is one of the main factors supporting the epidemic of leaf blight. Weather changes will affect the development of pathogens and affect the development of disease in the field. This research aimed to find out the effect of weather elements (air temperature, humidity, sunlight intensity, rainfall, number of rainy days) on the intensity of the taro leaf blight attack. The results showed that weather elements had a significant correlation with the intensity of taro leaf blight disease. Air temperature and sunlight intensity showed negative correlations while air humidity, rainfall and the number of rainy days were positively correlated with the disease intensity. The results of this path analysis showed that air humidity had the most significant effect of the weather elements on the intensity of taro leaf blight both directly and indirectly.